West Nile Virus Infection and its Neurological Manifestations - Madden, Ken (Marshfield Clinic Research Foundation, 2003)
The West Nile virus caused an epidemic of meningoencephalitis in Midwest North America during 2002. The peak incidence coincided with the highest activity period of mosquito vectors in affected states. This epidemic followed recent established trends, not only of increased central nervous system involvement by the virus, but also increased incidence of dramatic neuromuscular impairment. Two cases are presented which illustrate the most concerning types of neuromuscular sequelae, diffuse weakness leading to respiratory insufficiency, and the development of focal weakness similar to poliomyelitis. The epidemiology and clinical characteristics of West Nile virus infection are also reviewed. Concern is expressed regarding the possibility of epidemics in other Midwestern states during future seasons of increased mosquito activity.